2016
DOI: 10.1136/gutjnl-2016-312904
|View full text |Cite
|
Sign up to set email alerts
|

The active bacterial assemblages of the upper GI tract in individuals with and without Helicobacter infection

Abstract: The detailed analysis of the active global bacterial communities from the five distinct sites of the upper GI tract allowed for the first time the differentiation between host effects and the influence of sampling region on the bacterial community. The influence of spp on the global community structures is striking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
169
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 38 publications
(54 reference statements)
21
169
6
5
Order By: Relevance
“…A study by Klymiuk et al reported the effect of H pylori infection on the gastric microbiota and found that the number of Lactobacillus , Streptococcus , Acinetobacter , Prevotella, and Bacteroides genera was remarkedly decreased, while Helicobacter was increased in H pylori ‐positive samples. Another study compared the active bacterial communities in the stomach with and without Helicobacter infection and found that the stomach biopsies in individuals infected with H pylori had higher abundance of Helicobacter but lower abundance of Prevotella and Streptococcus . Because H pylori infection induces dysbiosis of the gastric microbiota, the present study demonstrated that eradication therapy could partially restore the balance of the microbiome.…”
Section: Discussionmentioning
confidence: 52%
“…A study by Klymiuk et al reported the effect of H pylori infection on the gastric microbiota and found that the number of Lactobacillus , Streptococcus , Acinetobacter , Prevotella, and Bacteroides genera was remarkedly decreased, while Helicobacter was increased in H pylori ‐positive samples. Another study compared the active bacterial communities in the stomach with and without Helicobacter infection and found that the stomach biopsies in individuals infected with H pylori had higher abundance of Helicobacter but lower abundance of Prevotella and Streptococcus . Because H pylori infection induces dysbiosis of the gastric microbiota, the present study demonstrated that eradication therapy could partially restore the balance of the microbiome.…”
Section: Discussionmentioning
confidence: 52%
“…Due to the stability of the DNA molecule even in the acidic environment of the stomach, 16S DNA sequencing does not provide information on whether the bacteria are still viable and metabolically active. Sequencing of 16S rRNA after reverse transcription to DNA is one approach to overcome this limitation and to allow for the characterization of the active bacterial assemblages . Using this technique, Parsons et al studied the gastric microbiota of 75 individuals with H pylori ‐induced atrophic gastritis, autoimmune atrophic gastritis and PPI use, conditions associated with similar levels of hypochlorhydria, but different risks and types of gastric cancer—specifically neuroendocrine and adenocarcinoma.…”
Section: Resultsmentioning
confidence: 95%
“…Among these, an uncultured species related to the extremophile Deinococcus was discovered as well as members of the hypothetical phylum of enigmatic uncultured bacteria—TM7—referred to as ‘microbial dark matter’ . Several studies have also detected representatives of other uncultured bacteria designed as hypothetical phylum SR1 . Still, there was a significant overlap with previous cultivation findings, mainly because gastric microbes are oxygen tolerant and therefore more readily cultured and described compared to the predominantly anaerobic colonic microbiota.…”
Section: Introductionmentioning
confidence: 95%